Tensile test fractography of subzero treated EN24 alloy steel. (2021) - Karthikeyan, KMB.; Yuvaraj, C.; Balasubramanian, T.
Abstract: Material processing techniques are widely employed for enhancing the metallurgical and functional behavior of materials. The generalized material treatments are replaced with tailor-made processes to enhance thermal, structural, dynamic, and environmental properties during on and off the service life. An attempt has been made to investigate the effect of thermal cycling involving cryogenic treatment on EN24 steel. The effect of cryogenic treatment on the microstructure and material properties of EN24 steel was analyzed and interpreted concerning material ductility. Unlike, other surface treatments, the cryogenic treatment affect the material core properties and provide a stable microstructure, without affecting the ductility of the material. The cryogenically treated (CT) EN24 alloy steel exhibited a microstructure with primary and secondary carbides with a substantial reduction in retained austenite. Tensile test fractography of cryogenically treated EN24 steel revealed a mixed-mode of ductile and brittle fracture. The cryogenically treated samples exhibited ductility without sacrificing hardness. The shallow cryogenically treated (SCT) samples exhibited higher impact strength than the deep cryogenically treated (DCT) EN24 alloy steel. A substantial improvement in tensile strength with a reduction in elongation was observed for cryogenically treated samples. Thus cryogenic treatment can complement conventional heat treatment of engineering steels with controlled treatment conditions.